Bioassay-guided isolation and structure elucidation of anti-mycobacterium tuberculosis compounds from Galatella grimmii (Regel & Schmalh.) Sennikov - Abolfazl Shakeri; Mehrangiz Tajvar; Ghazaleh Tabriznia Tabrizi; Saman Soleimanpour; Javid Davoodi; Javad Asili; Mohammad Sadegh Amiri; Seyed Ahmad Emami (BMC, 2024)
Abstract Background Galatella is a genus in the family Asteraceae, represented by 35-45 species. Considering the high effectiveness of the ethyl acetate (EtOAc) fraction of G. grimmii against Mycobacterium tuberculosis (MIC = 0.5 µg/mL), a bioassay-directed fractionation of this extract was carried out. Methods The methanolic extract of the aerial parts of G. grimmii was obtained using maceration, then it was suspended in water and partitioned with petroleum ether, dichloromethane (CH2Cl2), EtOAc, and n-butanol (n-BuOH), successively. The most potent fraction (EtOAc), was selected for further isolation by Sephadex LH-20 and semi-preparative HPLC to obtain active compounds. Results Fractionation of the EtOAc solvent fraction resulted in the characterization of five compounds, among them, compounds 1 and 2 showed the highest anti-mycobacterial effects with MICs of 0.062 and 1.00 µg/mL against H37Rv M. tuberculosis, respectively, which were higher than those of rifampin (MIC of 1.25 µg/mL) and isoniazid (MIC of 0.31 µg/mL), as positive controls. Also, compound 1 ​​inhibited all tested strains of drug-resistant Mycobacterium (MDR and XDR). Notably, the isolated compounds have been reported for the first time from G. grimmii. Conclusion Due to the potent anti-mycobacterial effect of isolated compounds from G. grimmii, this study could pave the way for developing a novel class of natural anti-tuberculosis compounds.